Making Child’s Spirit Power More Active Using Ethnomusic - Jonilienė, Marija (Acta Paedagogica Vilnensia, 2003)
In this article it is analysed the possibilities of making child’s spirit power more active using ethno-music. Ethno-music is an art of sounds and can have a deep influence on the emotions of a human being. The primitive means of expressions and simple forms as well the near and understandable heroes of the poetic text suits not only for the elementary abilities, knowledge and skill training but as well has a great influence on the total education of the personality. Small children are very emotional so the influence of ethno-music on them is very great. Musical activity grounded by ethno-music, induces child’s power of spirit to be active. It is manifested in child’s communication, moral behaviour with adults, other children, animals, nature, toys, things and so on. The article also reveals, that very important role educating child’s moral behaviour belongs to ethno-music. ln poetical songs, games texts, in simple melodies of children songs we can find a lot of good and moral behaviour elements. The data of completed upbringing experiment confirms that ethno-music has very big importance making child’s spiritual power more active.